Student compliance in paying zakat: Do zakat literacy and awareness matter? - Malik, Abdul; Alrasyid, Harun; Kamaruddin, Muhammad Musyawir (Faculty of Business & Economics, Universitas Islam Indonesia, 2024)
Purpose – This study analyzes how zakat literacy and awareness affect compliance with zakat payments among Islamic students. Zakat literacy involves understanding zakat’s concept, types, calculation, and distribution, while awareness includes recognizing zakat’s importance as a religious and socioeconomic duty.Methodology – This study employed a quantitative approach using primary data collected from second- and fourth-semester students at Muhammadiyah University of Makassar through purposive sampling and questionnaires distributed to 116 individuals via WhatsApp groups. Data analysis was conducted using multiple linear regression with SPSS Version 26, chosen for its comprehensive statistical tools and user-friendly interface. Findings – Data analysis revealed that both zakat literacy and awareness had a positive and significant effect on compliance with paying zakat. Students with higher levels of zakat literacy and deeper awareness of the benefits of zakat are more motivated and consistent in paying zakat, according to Sharia provisions.Implications – This study highlights the importance of zakat education and counseling in universities to enhance literacy and awareness, which can ultimately increase compliance with paying zakat. This increase in compliance supports the achievement of Zakat’s social and economic goals in reducing poverty and social inequality.Originality – This study makes a unique contribution by focusing on the role of zakat literacy and awareness among students, a topic that has been underexplored. These findings can inform the development of more effective zakat education programs at the university level.